Queen of flowers and pearls : a novel - Ghermandi, Gabriella, 1965- (Global African voices., 2015)
"Mahlet, a young Ethiopian girl with a gift for storytelling, has a special bond with Yacob, the oldest in her household. When Yacob tells her stories of how he and the other warriors fought in the resistance against the Italian occupation of Ethiopia, Mahlet vows to become the keeper and teller of her family's stories. From the time of Menelik to the present, Mahlet's long voyage through time and space links thousands of stories between Africa and Europe. Intensely personal, this powerful and beautifully narrated novel tells the story of the Italian occupation of Ethiopia as well as of others around the globe who have suffered under colonialism or have been forcibly exiled from their homelands"--Provided by publisher